The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c6cp06627e
|View full text |Cite
|
Sign up to set email alerts
|

Infrared dynamics study of thermally treated perfluoroimide acid proton exchange membranes

Abstract: The temperature induced dehydration process of the 3M Brand perfluoroimide acid (PFIA), an advanced proton exchange membrane for fuel cells, was studied by in situ infrared spectroscopy to understand proton transport processes under conditions of low hydration levels. A comprehensive assignment of the vibrational bands of PFIA in the mid infrared region is provided. Investigation of the kinetics in conjunction with 2D correlation spectroscopy methods revealed the sequential process of the hydration and dehydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 57 publications
(102 reference statements)
8
28
0
Order By: Relevance
“…The Nafion vehicular proton conductivity values were calculated by using the previously published Nafion simulated vehicular diffusivities for hydronium ions [26][29] [30]. The PFIA vehicular proton conductivities are observed to be higher than those of Nafion at both T=300 K and T=353 K. This agrees qualitatively with the experimental trends seen at T=300 K [20] and T=353 K [22].…”
Section: Column 4)supporting
confidence: 68%
See 1 more Smart Citation
“…The Nafion vehicular proton conductivity values were calculated by using the previously published Nafion simulated vehicular diffusivities for hydronium ions [26][29] [30]. The PFIA vehicular proton conductivities are observed to be higher than those of Nafion at both T=300 K and T=353 K. This agrees qualitatively with the experimental trends seen at T=300 K [20] and T=353 K [22].…”
Section: Column 4)supporting
confidence: 68%
“…1(a)) [18] have been developed to serve this purpose. There have been experiments [20] which have shown that the average current through a PFIA membrane is significantly higher than that in a Nafion™ 212 membrane 2 , which has an EW of 1100 [21], at 300 K. It has also been observed in experiments [22] that PFIA has significantly higher proton conductivity than NAFION™ NR211 3 , which has an EW of 990-1050 [23], across a wide range of hydration levels at 353 K. For instance, PFIA and Nafion have a proton conductivity of 0.1 S/cm [22] and 0.05 S/cm [22] for 50% RH at 353 K respectively.…”
Section: Introductionmentioning
confidence: 72%
“…This important observation means that the proton dissociation process—and subsequent H‐bonding to water molecules to form protonic species—is completely different when the sulfonyl imide moiety is used instead of sulfonic acid (i.e., a peculiar hydronium‐free ionization–hydration mechanism characterizes the TFSI polymer). A very different dissociation process of sulfonic and sulfonyl imide acids was also reported with perfluoro ionene chain‐extended ionomers from 3 m even if the side‐chain chemistry promotes H‐bonds between acid functions and H‐bonding configurations of water that facilitate proton dissociation …”
Section: Resultsmentioning
confidence: 79%
“…The analysis of FIR/MIR data was combined, on one hand, with the knowledge acquired on Nafion membrane using the same in situ protocol and experimental techniques [52] and,o nt he otherh and, with the data availableo nb is(trifluoromethanesulfonyl)imide acid (HTFSI) and bis(trifluoromethanesulfonyl)imide anion (TFSI À ). [28,53,54] As our goal was to investigate the mechanisms of proton dissociation, the formationo fp rotonic species and the role/state of water molecules( in particulari nt he very early stageso fh ydration), we focusedo ur attentiono nt he vibrational bands of H 2 O( connectivity band at 200 cm À1 ;b ending at 1740 cm À1 ;s tretching at % 3400 cm À1 ), [55] protonic species (stretching of OÀHb ond in H 3 O + at 2700 cm À1 ,i nter-molecular signature for SO 3 À ·H 3 O + interactions at 250 cm À1 ; [53,56] Zundel ChemSusChem 2020, 13,590 -600 www.chemsuschem.org ion (H 5 O 2 + )b ands at 150 cm À1 and 1740 cm À1 ), [57] andH TFSI (NÀHa nd SO 2 )and TFSI À (NÀHa nd SO 2 ). [53] Figure 4d isplays the in situ absorbance of Si 15/15i onomer in the MIR [top panels, ranges (a) 2400-3200 cm À1 and (c) 1100-1600 cm À1 ]a nd FIR [bottom panels, ranges (b) 700-910 cm À1 and (d) 450-650cm À1 ].…”
Section: Protonation and Transport Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation